Revealing Local Knowledge of Sundanese People of Toponyms in The Western Bandung-North Area - Fasya, Mahmud; Kurniawan, Eri; Nurhadi, Jatmika; Sudana, Undang; Gilang Sari, Dini; Rahmawati, Rahmawati (Jurnal Arbitrer, 2023)
This study examines the classification and function of toponyms to reveal the local knowledge of Sundanese people in the western Bandung-North area. This research uses anthropological linguistic theory. The data of this research are lexicon in toponyms based on local knowledge in the western Bandung-North area. The data is sourced from several community components consisting of village elders and ordinary people. The study incorporates four methods for data collection, which are participant observation, participatory conversation observation, interviews, and documentation. These techniques are chosen based on their ability to gather comprehensive, accurate, and reliable data. The results show that there are five classifications of toponyms, namely (1) hydrological-biological characteristics, (2) hydrological-state characteristics, (3) geomorphological-biological characteristics, (4) geomorphological-state characteristics, and (5) state characteristics. This research also shows that the lexicon in toponyms in the western Bandung-North area portrays the closeness of humans to nature, humans to humans, and humans to their God. In addition, Sundanese people in the western Bandung-North area also have local knowledge about ethnoecology, which is recorded in the toponyms in the area. This local knowledge of ethnoecology has benefits as an effort to maintain the terrestrial ecosystem, which is one of the pillars of environmental development in the context of the Sustainable Development Goals (SDGs).